Effect of managed transition on mental health outcomes for young people at the child–adult mental health service boundary: a randomised clinical trial. Issue 6 (29th April 2023) - Singh, S. P.; Tuomainen, H.; Bouliotis, G.; Canaway, A.; De Girolamo, G.; Dieleman, G. C.; Franić, T.; Madan, J.; Maras, A.; McNicholas, F.; Paul, M.; Purper-Ouakil, D.; et al.
Abstract: Background: Poor transition planning contributes to discontinuity of care at the child–adult mental health service boundary (SB), adversely affecting mental health outcomes in young people (YP). The aim of the study was to determine whether managed transition (MT) improves mental health outcomes of YP reaching the child/adolescent mental health service (CAMHS) boundary compared with usual care (UC). Methods: A two-arm cluster-randomised trial (ISRCTN83240263 and NCT03013595) with clusters allocated 1:2 between MT and UC. Recruitment took place in 40 CAMHS (eight European countries) between October 2015 and December 2016. Eligible participants were CAMHS service users who were receiving treatment or had a diagnosed mental disorder, had an IQ ⩾ 70 and were within 1 year of reaching the SB. MT was a multi-component intervention that included CAMHS training, systematic identification of YP approaching SB, a structured assessment (Transition Readiness and Appropriateness Measure) and sharing of information between CAMHS and adult mental health services. The primary outcome was HoNOSCA (Health of the Nation Outcome Scale for Children and Adolescents) score 15-months post-entry to the trial. Results: The mean difference in HoNOSCA scores between the MT and UC arms at 15 months was −1.11 points (95% confidence interval −2.07 to −0.14, p = 0.03). The cost of delivering the intervention was relatively modest (€17–€65 per service user). Conclusions: MT led to improved mental health of YP after the SB but the magnitude of the effect was small. The intervention can be implemented at low cost and form part of planned and purposeful transitional care.